Prospective, randomized study of conventional versus HybridKnife endoscopic submucosal dissection methods for the esophagus: an animal study - Fukami, Norio; Ryu, Chang Beom; Said, Sherif; Weber, Zachary; Chen, Yang K. (Gastrointestinal endoscopy, 2011)
Endoscopic submucosal dissection (ESD) increases en bloc and histologically complete resection rate of neoplastic mucosal tumors but is technically more demanding than EMR. Limited data are available comparing the efficacy and safety of a new ESD designed to overcome these limitations and conventional ESD (C-ESD) techniques. To compare the safety, efficacy, and operation time of the new HybridKnife ESD (HK-ESD) with C-ESD in the esophagus. Prospective, randomized, controlled study. Animal research laboratory. Seventeen anesthetized Yorkshire pigs. Removal of a 4-cm length of half-circumference esophageal mucosa by C-ESD with Hook knife or Flexknife versus HK-ESD. Procedure time, en bloc and complete resection rate, and complications (bleeding and perforation). All resections were completed en bloc. Procedure time was shorter in C-ESD. However, it was similar after 12 procedures. Significantly more bleeding occurred during C-ESD (28 vs 12, P = .0007). Histological muscularis propria injuries occurred with equal frequency (16 vs 17) and were mostly seen during the first 11 procedures. There were 3 perforations (2 endoscopic, 1 histological), all with C-ESD. Nonsurvival study, use of 2 conventional knives, no training period for a new procedure. The HK-ESD technique was equally effective as the C-ESD technique for successful en bloc resection and was safer with less bleeding and perforation. Although procedure time was longer in HK-ESD, the difference became nonsignificant after 12 procedures.